Answer:
1) 20 : (-2) + 5 = -5
2) 7 + (-5) × 5 = -18
3) 13 × (-4) - (-3) = -49
4) 8 + (-12) : 4 = 5
5) 30 : (-6) × (-2) = 10
Explanation:
* Lets revise the order of the operation
- In any problem contains addition , subtraction , multiplication and
division, then the order of operations is multiplication or division
whose come first at first and addition or subtraction whose come
first at second
* Lets solve the problem
1) 20 : (-2) + 5
- At first solve 20 : (-2) ⇒ (20 ÷ (-2))
∵ 20 : (-2) = -10
∴ 20 : (-2) + 5 = -10 + 5
∵ -10 + 5 = -5
∴ 20 : (-2) + 5 = -5
2) 7 + (-5) × 5
- At first solve (-5) × 5
∵ (-5) × 5 = -25
∴ 7 + (-5) × 5 = 7 + (-25)
∵ 7 + (-25) = -18
∴ 7 + (-5) × 5 = -18
3) 13 × (-4) - (-3)
- At first solve 13 × (-4)
∵ 13 × (-4) = -52
∴ 13 × (-4) - (-3) = -52 - (-3)
∵ - (-3) = + 3
∴ 13 × (-4) - (-3) = -52 + 3
∵ -52 + 3 = -49
∴ 13 × (-4) - (-3) = -49
4) 8 + (-12) : 4
- At first solve (-12) : 4
∵ (-12) : 4 = -3 ⇒ (-12 ÷ 4)
∴ 8 + (-12) : 4 = 8 + (-3)
∵ 8 + (-3) = 5
∴ 8 + (-12) : 4 = 5
5) 30 : (-6) × (-2)
- At first we will start with the division because it becomes first
∵ 30 : (-6) = -5
∴ 30 : (-6) × (-2) = (-5) × (-2)
∵ (-5) × (-2) = 10
∴ 30 : (-6) × (-2) = 10